The Influence of Service MSMEs and Service Design on Value Co-Creation through Experiential Authenticity in Tourism MSMEs - Sinurat, Theresia; Manalu, Santi Agustina (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This research aims to analyze the influence of Service MSMEs and Service Design on Value Co-Creation through the mediating role of Experiential Authenticity in tourism MSMEs in Samosir Regency. The study employed a quantitative approach with an explanatory research design. Data were collected from 130 tourists who had interacted directly with tourism MSME services in Samosir Regency using purposive sampling techniques. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that Service MSMEs have a positive and significant influence on Experiential Authenticity. In addition, Service Design was also found to positively and significantly influence Experiential Authenticity. Furthermore, Experiential Authenticity has a positive and significant influence on Value Co-Creation. The results suggest that the quality of service interactions, integration of local cultural values, and well-structured service designs contribute to the formation of authentic tourism experiences and strengthen tourists’ participation in the value creation process. This research contributes to the development of tourism marketing literature within the perspective of Service-Dominant Logic by explaining the role of authentic experiences in encouraging Value Co-Creation in tourism MSMEs.